Linkages between the U.S. and Asia-Pacific Exchange Traded Funds (ETF) Markets: Evidence from the 2007-2008 Global Financial Crisis - Bum Suk Kim (Asian Academy of Management Journal of Accounting and Finance, 2011)
This paper examines co-integration and spillover effects between U.S. and Asia-Pacific stock markets using nine Exchange Traded Funds (ETFs) over the period from 7 January 2004 to 30 September 2010, with sub-samples of before and after the 2007–2008 global financial crisis. The nine ETFs include: SPDR, TOPIX, KODEX200 (KODEX), Tracker Fund of Hong Kong (TraHK), Polaris Taiwan Top 50 Tracker Fund (TT), SPDR S&P/ASX 200 Fund (STW), StreetTRACKS Straits Times Index Fund (STI), SmartFONZ (FNZ), and China 50 ETF. The co-integration analysis shows that there is a co-integration relationship between SPDR and TraHK, STW, STI, and FNZ before and after the global financial crisis. However, TOPIX shows little co-integration relationship with SPDR. In the case of KODEX and TT, no co-integration relationship is found before the crisis; however, it is found after the crisis. Before the crisis, SPDR co-integrated with China 50, but after the crisis the co-integration relationship weakened. The Granger causality tests indicate that, although U.S. stock markets lead Asia-Pacific stock markets, Asia-Pacific stock markets do not exert the same influence. GARCH tests show that there are significant spillover effects between the U.S. and Asia-Pacific stock markets. This paper confirms the fact that, since the 2007–2008 global financial crisis, the degree of co-integration and spillover effects has generally grown stronger.